The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2224/sbp.2008.36.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Dependence of Female Students and Perceived Parental Rearing Attitudes

Abstract: Using a written questionnaire we surveyed a sample population of 155 female students, and investigated the associations between mobile phone dependence and perceived parental rearing attitudes. Participants completed the Mobile Phone Dependence Questionnaire (MPDQ; Toda, Monden, Kubo, & Morimoto, 2004) and the Parental Bonding Instrument (PBI; Parker, Tupling, & Brown, 1979). In relation to maternal rearing attitudes, analysis of responses revealed a statistically significant difference in MPDQ scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 15 publications
(14 reference statements)
0
29
0
Order By: Relevance
“…Mobile phone addiction is also associated with maternal rearing attitudes in women. Females with higher levels of maternal protection are more likely to be addicted to mobile phones than those with lower levels of maternal protection (Toda et al, 2008).…”
Section: Technology Addictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mobile phone addiction is also associated with maternal rearing attitudes in women. Females with higher levels of maternal protection are more likely to be addicted to mobile phones than those with lower levels of maternal protection (Toda et al, 2008).…”
Section: Technology Addictionmentioning
confidence: 99%
“…Mobile phone addiction is associated with different factors such as personal habits and loneliness (Park, 2005;Toda et al, 2008). Ritualistic motives can explain mobile phone addiction better than instrumental motives (Park, 2005).…”
Section: Technology Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several problems have arisen from their use (Bianchi & Philips, 2005;Lee, Chang, Lin, & Cheng, 2014). Aside from physical problems with the head, neck, back, and hands, physiological problems such as stress, anxiety, depression, and addiction can also be seen related to mobile phone usage (Lu et al, 2011;Park, 2005;Toda et al, 2008;İnsani Yardım Vakfi [Humanitarian Relief Foundation], 2015).…”
Section: Smartphone Addictionmentioning
confidence: 99%
“…Some of these studies focus on smartphone effects (Toda et al, 2006) and the relationship between smartphone addiction and estimated hypothesized psychological factors (Beranuy, Oberst, Carbonell & Charmarro, 2009;Bianchi & Phillips, 2005;Ehrenberg, Juckes, White & Walsh, 2008;Ezoe et al, 2009;Ha, Chin, Park, Ryu & Yu, 2008;Hong, Chiu & Huang, 2012;Walsh, White, Cox & Young, 2011), social effecting factors (Walsh et al, 2011), mobile phone usage behavior (Billieux, Linden, & Rochat, 2008;Hong et al, 2012;Walsh et al, 2011) and family environmental factors (Toda et al, 2008). In the study conducted by Sevi, Odabasioglu, Genc, Soykal & Ozturk (2014), it was found that the increase in mobile phone usage was mostly related to self-insecurity, social incompatibility, frequent morale, and anxiety.…”
Section: Introductionmentioning
confidence: 99%